Utilization of Nipa Palm (Nypa fruticans) Leaf Extract as a Natural Preservative for Salted Three Spot Gourami (Trichopodus trichopterus) - Agustin Maharani Khairunisa; Riya Liuhartana Nasyiruddin Fuhrmann; Rih Laksmi Utpalasari; Zhulian Hikmah Hasibuan; RR. Dyah Paramitha Mentari; Steven Suryoprabowo; Muhammad Shoaib (CV Media Inti Teknologi, 2026)
Background: Salted three-spot gourami (Trichopodus trichopterus) is a traditional fish product that is susceptible to microbial spoilage and quality deterioration during storage. The use of plant-based bio-preservatives has been explored as an alternative to synthetic additives to improve product safety and shelf life. Aims: This study aimed to assess the effectiveness of nipa palm (Nypa fruticans) leaf extract at different concentrations as a natural preservative for salted three-spot gourami.Methods: The experiment was arranged in a Completely Randomized Design (CRD) with four treatments (0%, 10%, 15%, and 20%) and three replications. Parameters observed included moisture content, Total Plate Count (TPC), and organoleptic attributes (appearance, aroma, and texture).Results: The application of nipa palm leaf extract significantly (P < 0.05) affected moisture content, microbial growth, and sensory quality during storage. The 15% treatment (P2) produced the lowest moisture content throughout storage, reaching 19.83% on day 30. Microbial counts in all extract-treated samples remained within the maximum permissible limit of the Indonesian National Standard (≤1 × 10⁵ CFU/g), with the 20% treatment (P3) showing the lowest microbial load (1.0 × 10⁵ CFU/g) on day 30. Sensory evaluation indicated that extract-treated samples maintained acceptable appearance, aroma, and texture throughout storage, with better sensory stability than the untreated control.Conclusion: Nipa palm leaf extract effectively improved the storage quality of salted three-spot gourami. Although the 15% concentration (P2) achieved the greatest moisture reduction, the 20% concentration (P3) is recommended for practical application because it provided the strongest microbial inhibition while maintaining acceptable sensory quality during 30 days of storage.